2021
DOI: 10.1159/000514944
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of <b><i>Panax ginseng</i></b> on Genitourinary Syndrome in Postmenopausal Women: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: Background: Menopause and estrogen deprivation cause a rise in the number of urogenital tract complaints. Objective: This study was conducted to assess the effectiveness of ginseng on genitourinary syndrome. Methods: This randomized trial was conducted on 60 postmenopausal women with genitourinary syndrome. The participants were randomly allocated to ginseng and placebo groups twice daily for 4 weeks. Vaginal maturation index and vaginal pH were evaluated before and 4 weeks after intervention as the primary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…116 Besides, in a randomized, double-blind, crossover, placebo-controlled trial, exercise-stimulated muscle damage in physically active males was attenuated by American ginseng through modulation of the inflammatory response and lipid peroxidation. 117 A separate randomized, double-blind, crossover, placebo-controlled trial was conducted to assess the impact of P. ginseng on genitourinary syndrome in postmenopausal women, revealing an improvement in associated symptoms after four weeks of the study. Additionally, a four-week clinical trial demonstrated that Korean red ginseng reduced allergic symptoms and total immunoglobulin E levels in patients with allergic rhinitis compared to individuals receiving a placebo.…”
Section: Examples Of Some Common Herbs Scientifically Proven To Be Ef...mentioning
confidence: 99%
“…116 Besides, in a randomized, double-blind, crossover, placebo-controlled trial, exercise-stimulated muscle damage in physically active males was attenuated by American ginseng through modulation of the inflammatory response and lipid peroxidation. 117 A separate randomized, double-blind, crossover, placebo-controlled trial was conducted to assess the impact of P. ginseng on genitourinary syndrome in postmenopausal women, revealing an improvement in associated symptoms after four weeks of the study. Additionally, a four-week clinical trial demonstrated that Korean red ginseng reduced allergic symptoms and total immunoglobulin E levels in patients with allergic rhinitis compared to individuals receiving a placebo.…”
Section: Examples Of Some Common Herbs Scientifically Proven To Be Ef...mentioning
confidence: 99%